A model of uniaxial implant seating by impaction. (November 2021) - Bishop, N.E.; Wright, P.; Dudrey-Harvey, C.; Preutenborbeck, M.
Highlights Bishop et al: Validated model of implant seating by impaction. Easily measurable parameters identified that allow estimation of impacted implant seating. Dynamic behaviour of impacted implant systems is explained. Model will provide a basis for improving implantation systems and techniques. Abstract: Implants anchored by press-fit are predominantly implanted by impaction. This method allows sufficiently high forces to be generated easily by the surgeon. Suitable impaction should provide adequate implant seating without damaging the patient (tissues), the implant and implantation system, or the surgeon. However, issues have been documented for all of these factors. In this study a model to predict implant seating is developed, given an applied impaction impulse, the mass of the accelerated components and the push-in resistance force. The model was validated against experimental data for a contemporary femoral stem implanted in a polyurethane foam surrogate for bone, with the input parameters varied. The model tended to overestimate seating but represented seating patterns well. The model can be used to estimate implant seating using easily measured parameters and could be useful in the design of implantation systems, and in optimising impaction strategies.